KUALITAS PAPAN PARTIKEL DARI CAMPURAN SABUT KELAPA DAN PARTIKEL MAHONI DENGAN BERBAGAI VARIASI KADAR PEREKAT PHENOL FORMALDEHIDA - Heber Fransiskus; Rudi Hartono; Tito Sucipto (Peronema Forestry Science Journal, 2015)
Coco fiber and mahogany can be used as raw material for the manufacture of particle board. Quality of particle board was affected by several things. One of them was affected by particle’s composition and adhesive levels. The aim of this research was to evalated the affect of particle’s composition and adhesive levels, and also to find the best treatment. The dimension of sample test was 25x25x1 cm with a density target of 0.7 g/cm3. The composition between coco fiber and mahogany were 60:40, 70:30 and 80:20. The adhesive used were phenol formaldehyde with composition of 10%, 12.5% and 15%. Testing the quality of particle board refers to the standard JIS A 5908-2003. The results showed that some of the test on particle board not fulfiled the standards of JIS A 5908-2003, such asMOE and MOR. However, all of density test on particle board had fulfilled the standard. Moisture content test on particle board compositionof 80:20andadhesive content of 12.5% had fulfilled the standard. Thickness swelling test on particle board compositionof 60:40and adhesive content of 15% had fulfilled the standard. And also internal bond test on particle board compositionof 60:40 and 70:30 with adhesive content of15% had fulfilled the standard. The best treatment of this research were a particle board made from compostion of 60:40 and adhesive content of 15%. Keywords: particle board, coco fiber, mahogany, physical and mechanical properties, phenol formaldehyde